1976
DOI: 10.1161/01.cir.53.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical configuration of the His bundle and bundle branches in the human heart.

Abstract: The relationships among the His bundle, the origin of both bundle branches, and the interventricular (IV) septum were examined histologically in 32 human hearts, and the entire bundle branch systems were delineated in 13 of these. The His bundle in five hearts traversed the right IV septal crest, and the LBB origin was a very narrow stem (maximum 1.5 mm in cross-section) crossing from right to left through the inferior margin of the membranous septum. Proximal LBB anatomy was extremely variable, demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(122 citation statements)
references
References 21 publications
(8 reference statements)
7
110
0
Order By: Relevance
“…An explanation for the great variability in the electrical axis in relation to the anatomical axis of the heart may be a great interindividual variability in how the Purkinje network of the heart is organized. It has been shown that there is a considerable variation in the architecture of the distal conduction system (27). Furthermore, the stronger age-dependence of electrical axis than of anatomical axis found in the frontal plane in present study, might partly be explained by increased fibrosis and fatty infiltration in the conduction system with increased age (28).…”
Section: Discussionmentioning
confidence: 38%
“…An explanation for the great variability in the electrical axis in relation to the anatomical axis of the heart may be a great interindividual variability in how the Purkinje network of the heart is organized. It has been shown that there is a considerable variation in the architecture of the distal conduction system (27). Furthermore, the stronger age-dependence of electrical axis than of anatomical axis found in the frontal plane in present study, might partly be explained by increased fibrosis and fatty infiltration in the conduction system with increased age (28).…”
Section: Discussionmentioning
confidence: 38%
“…Massing and James [60] found this position in 62.5% of normal human hearts of various age. Left sided His bundle has been described in association with sudden death in previously healthy people [72,82] and in asthmatics [83].…”
Section: Left Sided His Bundlementioning
confidence: 86%
“…The RV completes its depolarization later than the LV. However, these isochrones may not be identical, as the conduction systems of different human hearts do not have identical structures [8]. using the proposed conduction system and the modified RDE.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate heart electrical activation, both structures must be identified, especially the conduction system, as it initiates the activation. The most common reference models used to identify the ventricular conduction system of the heart are those described by Tawara [7], Massing et al [8], and Durrer et al [9]. Modeling of the ventricular conduction systems involves either assigning the early activation sites according to the measurements of Durrer et al [10][11][12][13] or building a network according to the heart anatomical structure and activation isochrones [14][15][16][17].…”
Section: Heart Tissue Decompositionmentioning
confidence: 99%
See 1 more Smart Citation